Identifikasi Keanekaragaman Jenis Burung di Kawasan Restorasi Resort Sei Betung, Taman Nasional Gunung Leuser / (Identification Diversity of Bird Species in Restoration Area at Sei Betung Resort, Gunung Leuser National Park) - Duma Fransisca Sihotang; Pindi Patana; Erni Jumilawaty (Program studi Kehutanan USU, 2013)
Forest damage in any ways will determine all of the organism inside include the birds. Forest restoration is a positive step that would help to recover back the forest. Bird is one of bio-indicator of forest condition. This research was needed not only to compare the diversity of birds between restoration area and primary forest (middle and edge forest), but also to know the species of birds which could adapt in both areas. The research was conducted in June – July 2012 at Sei Betung Resort, based on the IPA (Indices Ponctuels d’Abondence) or Point Count method. The result showed that bird diversity index in middle forest is 3,586 as well as in edge forest is 3,554. Both results are categorized as high diversity level, while the restoration area is categorized as middle diversity level with 3,095 index value. Some birds were founded in both areas such as Wreathed hornbill (Aceros undulatus), Emerald dove (Chalcophaps indica), Black magpie (Platysmurus leucopterus), Short-toed coucal (Centropus rectunguis ), Greater coucal (Centropus sinensis), Lesser coucal (Centropus bengalensis), Buff-rumped Woodpecker (Meiglyptes tristis), Rufous woodpecker (Celeus brachyurus), Red-breasted parakeet (Psittacula alexandri), Yellow-vented bulbul (Phycnonotus goiavier), Cream-vented bulbul (Pycnonotus simplex), Black-headed Bulbul (Pycnonotus atriceps), Red-whiskered bulbul (Pycnonotus jocosus), Ashy tailorbird (Orthotomus ruficeps), Rufous-tailed tailorbird (Orthotomus sericeus), Magpie robin (Copsychus saularis). Key words: bird diversity, bird adaptation, primary forest, restoration area